Design requirements for advertising on fashion fabrics printed for the Italian company Moschino Milano - Oday Ismael Ibrahim (Journal of Techniques)
The design of fabrics and fashion is an innovative art characterized by functional and aesthetic features, in which the designer strives to make the biggest impact on the forum and its aesthetic and aesthetic conviction. The aesthetic values, together with the functional value that the design is based on, play a role in meeting the requirements of the age and filling the needs of the consumer. The acquisition of fabrics and fashion which has reached its final stages through the technical development, and the technologies that were keeping pace with the movement of development, which is still evolving and varies according to the modern need, that the declaration differs in many differences in terms of application and means . , Advertising in newspapers, walls, magazines, newspapers, transport and also spread to fashion fabrics, which in each of these cases is trying to come close to achieving its objectives, namely to achieve contact with the delivery of the message to the recipients, as well as the promotion and objective in conveying the aesthetic and functional meaning of fabrics and fashion , A set of conclusions and conclusions were reached